Reversible SC‐SC Transformation involving [4+4] Cycloaddition of Anthracene: A Single‐Ion to Single‐Molecule Magnet and Yellow‐Green to Blue‐White Emission - Huang, Xin‐Da; Xu, Yan; Fan, Kun; Bao, Song‐Song; Kurmoo, Mohamedally; Zheng, Li‐Min (Angewandte Chemie International Edition, 2018)
In search of magneto‐optic materials, the mononuclear compounds LnIII(depma)(NO3)3(hmpa)2 (Ln=Dy, Gd) were synthesized. The anthracene moieties undergo [4+4] dimerization when irradiated at 365 nm without loss of crystallinity. The Dy compound switches from a single‐ion to a single‐molecule magnet with doubling of the spin reversal barrier energy and from yellow‐green to blue‐white emission. The dimerization is reversed by heating at 100 °C or partially on light irradiating at 254 nm. The results suggest that lanthanide phosphonates with anthracene are promising smart materials displaying synergistic magneto‐optic property. Pairing up: The mononuclear compound DyIII(depma)(NO3)3(hmpa)2 (depma= 9‐diethylphosphono‐methylanthracene, hmpa=hexamethylphosphoramide) undergoes reversible [4+4] photodimerization in a single‐crystal‐to‐single‐crystal manner. This process is accompanied by a change from a single‐ion to a single‐molecule magnet and from yellow‐green to blue‐white emission.